Effects of adhesive bond on active repair of aluminium plate using piezoelectric patch - Abuzaid, Ahmed; Shaik Dawood, Mohd. Sultan Ibrahim; Hrairi, Meftah (Trans Tech Publications Ltd., Switzerland, 2015)
Research activities on active repairs and stress control of structures using piezoelectric actuators and adhesive bond have received much attention in recent years. The function of the adhesive bond on active repair is to transmit the induced stresses by the piezoelectric actuator to the host structure in order to reduce the stress intensity on the crack front. Assessment of repair performance of adhesive bonds is done based on the transfer of the shear and peel stress concentration in the adhesive layer. In the present work, three-dimensional finite element analyses have been carried to understand the effects of adhesive properties on active repair performance of a cracked aluminium plate under mode I. Adhesive efficiency is evaluated by the stress intensity factor (SIF) as a fracture criterion. The results show that SIF varies inversely with the adhesive layer’s shear modulus.